Metodología para procesos de compras de materiales en obras menores de Ingeniería Civil - Morocho Granda, Xavier David (2017)
With the increase in civil infrastructure needs, the construction industry has had to increase the intensity of its operations by having to operate at increasing levels, construction companies must increase their administrative capacity. Although the construction has very unique patterns of operation that do not exactly follow conventional patterns of the process industry, it is necessary to recognize that the knowledge developed in it is susceptible to be used in construction companies. (Abad, Pérez, & Romero, 2005)